1984
DOI: 10.1111/j.1600-0447.1984.tb02476.x
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalography of DSM‐III borderline personality disorder

Abstract: The EEG's of hospitalized males with the sole diagnosis of borderline personality disorder (n = 37) were compared to those of a group with only dysthymic disorder (n = 31). Borderline patients were found to have significantly more marginal, definite, and combined (marginal and definite) abnormalities on the EEG. The most prevalent abnormality in the borderline was slow-wave activity. The mixture of wave frequencies occurring in the electroencephalogram, known as fusing, occurred significantly more often in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
0
1

Year Published

1985
1985
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 21 publications
5
14
0
1
Order By: Relevance
“…As early as the mid-1980s, the presence of significant sEEG abnormalities in BPD patients was well documented. Snyder and Pitts [13] showed that patients with BPD have a significantly higher rate of both definitive and less definitive EEG abnormalities when compared to a group with dysthymic disorders. Abnormalities (mainly slowing) were most frequently bilateral and of frontal, temporal or frontotemporal distribution.…”
Section: Episodic Impulsive or Aggressive Behaviormentioning
confidence: 98%
“…As early as the mid-1980s, the presence of significant sEEG abnormalities in BPD patients was well documented. Snyder and Pitts [13] showed that patients with BPD have a significantly higher rate of both definitive and less definitive EEG abnormalities when compared to a group with dysthymic disorders. Abnormalities (mainly slowing) were most frequently bilateral and of frontal, temporal or frontotemporal distribution.…”
Section: Episodic Impulsive or Aggressive Behaviormentioning
confidence: 98%
“…The symp toms of the borderline personality disorder may reflect cortical immaturity and may tend to improve as the patient ages [8], A signifi cant correlation between abnormal EEG and diminished social interaction, developmental delay, and impulsivity has been noted in chil dren [9].…”
Section: Discussionmentioning
confidence: 99%
“…H á vá rias razõ es para tal teoria: 1) a instabilidade afetiva presente em um grande número desses pacientes muitas vezes se assemelha a um quadro misto; 2) muitos pacientes com TPL apresentam descargas epileptóides em eletroencefalogramas, o que pode representar um tipo de efeito kindling, q u e e s t á h i s t o r i c a m e n t e a s s o c i a d o à fisiopatologia dos transtornos bipolares do humor 18,19 ; e 3) alguns autores demonstraram piora do descontrole comportamental após o tratamento de pacientes limítrofes com amitriptilina, o que pode representar um f e n ô m e n o s e m e l h a n t e a e p i s ó d i o s hipomaníacos, comumente induzido por antidepressivos tricíclicos em pacientes com transtorno bipolar do humor 20 . Assim, se a h i p ó t e s e d e q u e p a c i e n t e s c o m T P L pertencem ao grupo de transtornos do espectro bipolar estiver realmente correta, espera-se que tais pacientes respondam favoravelmente às drogas estabilizadoras do h u m o r , q u e sã o o n ú c l e o p r i n c i p a l d e psicotrópicos empregados no manejo do transtorno bipolar do humor 21 .…”
Section: Estabilizadores Do Humorunclassified